Epidemiology of uterine fibroid in black African women: a systematic scoping review - Imran O Morhason-Bello; Clement A Adebamowo (BMJ Open, 2022)
Objective Studies, mainly from high-income countries, suggest that there are ethnic and racial variations in prevalence of uterine fibroids (UF). However, there have been few studies of the epidemiology of UF in sub-Saharan Africa (SSA). We reviewed published articles on the epidemiology of UF in SSA.Design This was a scoping review of literature.Settings We searched three databases (PubMed, African Wide Information (EBSCO) and African Journals OnLine (AJOL)). The search for eligible articles was conducted between December 2019 and January 2021.Primary and secondary outcome measures To describe the reported prevalence/incidence of, and risk factors for UF in SSA.Results Of the 1052 articles retrieved, 9 met the inclusion criteria for review. The articles were from Nigeria (4/9), Ghana (2/9), Cameroon (1/9), Kenya (1/9) and South Africa (1/9). Two studies from pathology departments and three studies from radiology departments reported prevalence of UF. We did not find any study on the incidence or genomics of UF in SSA. Of the three studies that reported on the risk factors of UF, only one case–control study that was conducted using retrospective data of attendees at a gynaecological clinic conducted multivariable analysis.Conclusion There is lack of robust epidemiological studies of the prevalence, incidence and risk factors of UF in SSA. There is urgent need to study epidemiological and genomics risk factors of UF in SSA because UF is the most common gynaecological neoplasm in this population where it is associated with significant morbidity and occasional, usually perioperative, mortality.